Associations of Depressive Symptoms With Health Behaviors, Stress, and Self-assessed Health Status in Hawai'i: A Population Study. (March 2015) - Pomp, Sarah; Keller, Stefan; Maddock, Jay E.
Background. The aim of this cross-sectional study was to examine how depressive symptoms are associated with health behaviors, stress, and self-assessed health status in the population of Hawai'i. Methods. Randomized phone calls were made using computer assistant telephone interviews. A regression analysis with depressive symptoms as the outcome and sociodemographic variables, health behaviors, stress, and health status as predictors was conducted in 1483 adults. Results. Depressive symptoms were associated with stress (β = .32), alcohol consumption (β = .19), health status (β = −.10), fast food consumption (β = .06), avoidance of fat (β = −.06), and fruit and vegetable consumption (β = .06). Moreover, depressive symptoms were linked to being female (β = .06), being single (β = −.06), and being Caucasian compared with being Native Hawaiian (β = −.06) or Japanese (β = −.08). The overall explained variance was 22%. Conclusion. Depressive symptoms correlate with health risk behaviors and might be considered as a risk for chronic diseases.